Spheno-occipital synchondrosis fusion degree as a method to estimate age: a preliminary, magnetic resonance imaging study. Issue 2 (3rd March 2016) - Ekizoglu, Oguzhan; Hocaoglu, Elif; Can, Ismail Ozgur; Inci, Ercan; Aksoy, Sema; Sayin, Ibrahim
Abstract : The investigation of ossification regions in the skeletal system is a basic method for forensic age estimation. Although X-ray examination is commonly used in living subjects, magnetic resonance imaging (MRI) has gained importance because of its high resolution and its avoidance of radiation exposure. In this study, we investigated the utility of MRI in the evaluation of Spheno-occipital synchondrosis (SOS) fusion degree as a method to estimate age. The MRI findings of 1078 subjects (455 were male and 623 were female) aged 7–21 years were retrospectively evaluated according to a five-stage method. We found that SOS fusion started two years earlier in female subjects. The average age for stage 5 SOS fusion was 18.43 ± 1.84 years in male subjects and 17.78 ± 2.20 years in female subjects. Our results show that MRI in the determination of SOS fusion degree is an efficient non-invasive method to estimate age and avoids the disadvantages of radiation exposure incurred by X-ray or computed tomography examinations.